Improved spatial filtering velocimetry and its application in granular flow measurement*Project supported by the National Natural Science Foundation of China (Grant No. 11902190), the Construction Project of Shanghai Key Laboratory of Molecular Imaging (Grant No. 18DZ2260400), and the Fund from the Shanghai Municipal Education Commission, China (Class II Plateau Disciplinary Construction Program of Medical Technology of SUMHS, 2018-2020). (July 2020) - Kong 孔, Ping 平; Wang 王, Bi-De 必得; Wang 王, Peng 蓬; Zivkovic, V; Zhang 张, Jian-Qing 建青
Abstract : Spatial filtering velocimetry (SFV) has the advantages of simple structure, good stability, and wide applications. However, the traditional linear CCD-based SFV method requires an accurate angle between the direction of linear CCD and the direction of moving object, so it is not suitable for measuring a complex flow field or two-dimensional speed in a granular media. In this paper, a new extension of spatial filtering method (SFM) based on high speed array CCD camera is proposed as simple and effective technique for measuring two-dimensional speed field of granular media. In particular, we analyzed the resolution and range of array CCD-based SFV so that the reader can clarify the application scene of this method. This method has a particular advantage for using orthogonal measurement to avoid the angle measurement, which were problematic when using linear CCD to measure the movement. Finally, the end-wall effects of the granular flow in rotating drum is studied with different experimental conditions by using this improved technique.